Cultural Orientations of the Politics of Education in Ukraine (2010–2013): Ideology Strikes Back - Drozdovskyi, Dmytro (International Studies. Interdisciplinary Political and Cultural Journal, 2024)
In this article, the author has analysed educational reforms and educational policy in general, which was implemented in Ukraine during the presidency of Viktor Yanukovych. A few political cases were analysed, in particular the opposition of the National University of “Kyiv-Mohyla Academy” to the educational trends implemented by the Ministry of Education and Science of Ukraine under the leadership of Dmytro Tabachnyk. The manifestations of colonial policy in Ukrainian education, which were aimed at the rapprochement of Ukraine and Russia and the positioning of Ukraine as a colonial part of the imperial body, have been outlined. It has been discussed in what implicit way the colonial strategy was implemented in the educational reforms in Ukraine, in particular in the aspect of teaching humanitarian disciplines, e.g. Ukrainian literature. Forms of possible resistance to colonial strategies in the educational field, the principles of overcoming imperial pressure and intensifying the narrative of resistance, which made it possible to avoid further splitting of the Ukrainian identity in the imperial body, have been analysed. The legislative activity, which was focused on strengthening the status of the Russian language as a regional language, has been outlined. Linguistic colonial approaches at the level of legislative initiatives in language policy have been spotlighted, in particular in the Kivalov-Kolesnichenko Law.